A renaissance of color: New structures and building blocks for organic electronics. Issue 6 (7th January 2013) - Robb, Maxwell J.; Ku, Sung‐Yu; Brunetti, Fulvio G.; Hawker, Craig J.
Abstract Natural dyes and pigments like indigo and its derivatives valued for their bright colors and photochemical stability has been used since antiquity. Recently, the need for better performing materials in the organic electronics field has inspired a resurgence of these historical molecules and their subsequent transformation into new families of π‐conjugated building blocks used to construct new (macro)molecular semiconductors. This Highlight will explore the renaissance of notable building blocks including diketopyrrolopyrrole, (iso)indigo, benzodipyrrolidone, and benzodifuranone, as well as nonfullerene acceptor structures 9, 9′‐bifluorenylidene and quinacridone. In addition, as the organic electronics field continues to evolve, the design of molecules with precise structure and function embodies a new paradigm for the next generation of materials. Representative examples will be described that embrace this new model and point the direction for advanced technologies. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013